Protected cultivation in Maharashtra: determinants of adoption, constraints, and impact - Prakash P; Pramod Kumar; Amit Kar; Prabhat Kishore; Awani Kumar Singh; Sheela Immanuel (Agricultural Economics Research Review, 2023)
Under the National Horticulture Mission, protected cultivation is practised in the Pune and Nasik districts of Maharashtra. The cost of protected cultivation of rose and capsicum is over 300% of the cost of open cultivation; the gross return is 250% and net return 190%. Adoption is influenced by age, education, household income, landholding size, and distance to market. The high capital investment and cost of planting materials, and the incidence of pests and diseases were major constraints to adoption. Farmers will continue to adopt protected cultivation depending on their risk-bearing ability and government support.